Evaluación de emisiones de benceno en tres estaciones de servicio de combustibles líquidos en el distrito de San Juan Bautista 2023 - Tenazoa Ramírez, Ursula Paola (2024)
Benzene is a chemical compound widely used in the industry to manufacture a wide variety of products, including plastics, resins, detergents, medicines, pesticides, and other chemicals. The aim of our research was to determine whether benzene levels exceed the environmental air quality standard. For this purpose, the air absorption method using activated carbon tubes was employed, which were then analyzed in a gas chromatograph with a capillary column and an ionization detector. The results indicated that the amount of benzene emitted by each establishment was 357.6 liters, 284.9 liters, and 254.9 liters, respectively, and that the average detected level was 0.5482 ug/L. The conclusions determined that the levels of benzene volatilized at the service stations did not exceed the environmental air regulations.